Asteroseismological constraints on the coolest GW Virginis variable star (PG 1159-type) PG 0122+200 - Córsico, Alejandro Hugo (2007)
Aims. We present an asteroseismological study of PG 0122+200, the coolest known pulsating PG 1159 (GW Vir) star. Our results are based on an augmented set of the full PG 1159 evolutionary models recently presented by Miller Bertolami & Althaus (2006). Methods. We perform extensive computations of adiabatic g-mode pulsation periods on PG 1159 evolutionary models with stellar masses ranging from 0.530 to 0.741 M⊙. These models take into account the complete evolution of progenitor stars, through the thermally pulsing asymptotic giant branch phase and born-again episode. We constrain the stellar mass of PG 0122+200 by comparing the observed period spacing with the asymptotic period spacing and with the average of the computed period spacings. We also employ the individual observed periods to find a representative seismological model for PG 0122+200. Results. We derive a stellar mass of 0.626 M⊙ from a comparison between the observed period spacing and the computed asymptotic period spacing, and a stellar mass of 0.567 M⊙ by comparing the observed period spacing with the average of the computed period spacing. We also find, on the basis of a period-fit procedure, an asteroseismological model representative of PG 0122+200 that is able to reproduce the observed period pattern with an average of the period differences of δΠ̄i = 0.88 s and a root-mean-square residual of σδΠi = 1.27 s. The model has an effective temperature Teff = 81 500 K, a stellar mass M* = 0.556 M⊙, a surface gravity log g = 7.65, a stellar luminosity and radius of log(L*/L⊙) = 1.14 and log(R*/R ⊙) = -1.73, respectively, and a He-rich envelope thickness of Menv = 1.9 × 10-2 M⊙. We derive a seismic distance d ∼ 614 pc and a parallax π ∼ 1.6 mas. The results of the period-fit analysis carried out in this work suggest that the asteroseismological mass of PG 0122+200 could be ∼6-20% lower than hitherto thought, and in closer agreement (to within ∼5%) with the spectroscopic mass. This result suggests that a reasonable consistency between the stellar mass values obtained from spectroscopy and asteroseismology can be expected when detailed PG 1159 evolutionary models are considered.